The internationalization of sports clubs A qualitative study of internationalization in the sports industry - Dettmer, K. (2020)
Globalization has opened up new markets. Companies have now endless opportunities to expand their business reach with sports clubs being no exception. Internationalization in sports has its beginnings with foreign players joining a team and changed in 1995 with the Bosman ruling. After the Bosman ruling, the transfer of international players became easier. Not only can one notice the internationalization of sports teams by the transfer of players but also by the expansion of the sports itself. The NFL plays home games in London, the NBA in Mexico City and FC Bayern Munich has opened subsidiaries in the US and China. Yet, this all seems like the whole sports industry is expanding. However the influences behind this drive are unclear. The purpose of this thesis is to gain an understanding of internationalization in the sports industry. As the current literature indicates several gaps regarding the internationalization of sports clubs such as the limited view on one sport at the time or the data usage of clubs in their internationalization process, this thesis focuses on offering a broader picture. Therefore, the research question formulated for this thesis is: What influences the internationalization in the sports industry? For answering the research questions and fulfill the purpose of this thesis, an inductive approach was selected with a qualitative exploratory research study. By mixing the purposive and self-selected sampling, six semi-structured interviews were conducted among different sports clubs. The findings indicate that there are several different influences in the internationalization process of sports clubs. Leagues and their ambitions are one direct influence. Here, the leagues statutes seem to be guidelines for the clubs and their perspectives on growing. Another influence are the market conditions, where one can distinguish between the home market and foreign market conditions. There are some markets that do not allow much for further grow, as another sport is dominating the industry. For that reason, expanding internationally becomes necessary. Yet, some clubs see more potential on the home market to expand their scope and are thus, not thinking of internationalizing soon. Also influencing the internationalization are partnerships. Partnerships, either new or existing ones, offer the benefit of having knowledge or a business network the club can potentially benefit from. This study contributes to the literature of sports teams` internationalization by adding the underlying concept of influences in the process. Understanding the influences will not only support the eventual internationalization but also offers the opportunity to unite organizations in their efforts.